Does the Contrast Dispersion Pattern During Fluoroscopically Guided Cervical Transforaminal Epidural Steroid Injection Predict Short-Term Pain and Functional Outcomes? An Exploratory Analysis of Prospective Cohort Data. Issue 12 (29th September 2020) - Conger, Aaron; Sperry, Beau P; Cheney, Cole W; Kuo, Keith; Petersen, Russel; Randall, Dustin; Salazar, Fabio; Cunningham, Shellie; Henrie, A Michael; Bisson, Erica; Kendall, Richard; Teramoto, Masaru; et al.
Abstract: Summary of Background Data: No study has evaluated the relationship between contrast dispersion patterns and outcomes after fluoroscopically guided cervical transforaminal epidural steroid injection (CTFESI). Objectives: Determine whether contrast dispersion patterns predict pain and functional outcomes after CTFESI. Methods: Secondary analysis of data collected during two prospective studies of CTFESI for the treatment of refractory radicular pain. Contrast dispersion patterns visualized by true anteroposterior (AP) projections during CTFESIs were categorized by flow: 1) completely external to the lateral border of the neuroforamen (zone 1); 2) within the neuroforamen but without entry into the lateral epidural space (zone 2); and 3) with extension into the lateral epidural space (zone 3). At baseline and at 1 month post-CTFESI, neck pain, arm pain, and "dominant index pain" (the greater of arm or neck pain) were evaluated using a numeric rating scale (NRS); physical function was assessed using the Five-Item Version of the Neck Disability Index (NDI-5). Results: One-month post-CTFESI, neck pain, arm pain, and "dominant index pain" reductions of ≥50% were observed in 39.4% (95% confidence interval [CI], 28.2–51.8), 55.6% (95% CI, 43.0–67.5), and 44.1% (95% CI, 32.7–56.2) of participants, respectively. Regarding "dominant index pain, " 72.7% (95% CI, 40.8–91.2), 39.4% (95% CI, 24.2–57.0), and 37.5% (95% CI, 20.5–58.2) of participants reported ≥50% pain reduction when zone 1, zone 2, and zone 3 contrast flow patterns were observed. Contrast dispersion zone was not significantly associated with subgroup differences in neck pain, arm pain, or NDI-5 scores ( P >0.05). Conclusion: Improvements in pain and function 1 month after treatment with CTFESI did not differ significantly based on the contrast dispersion pattern. Future study is needed to confirm or refute these findings in other procedural settings, in broader patient populations, and with longer-term outcome assessment.